BK virus salivary shedding and viremia in renal transplant recipients - Dmitry José de Santana Sarmento; Michelle Palmieri; Gustavo Souza Galvão; Tânia Regina Tozetto-Mendoza; Cynthia Motta do Canto; Ligia Camera Pierrotti; Elias David-Neto; Fabiana Agena; Marina Gallottini; Claudio Sergio Pannuti; Maria Cristina Domingues Fink; Paulo Henrique Braz-Silva (University of São Paulo, 2019)
Abstract Objectives: This study aimed to verify the presence of polyomavirus BK (BKPyV) in the saliva of kidney transplant recipients and to correlate it with blood viremia. Material and Methods: We have conducted a cross-sectional study with a sample involving 126 renal transplant recipients. 126 samples of saliva and 52 samples of blood were collected from these patients. Detection and quantification of BKPyV were performed using a real-time PCR. To compare the presence of BKPyV in blood and saliva, the binomial proportion test was used. To verify associations between salivary shedding BKPyV and post-transplant periods (in months), the Mann-Whitney test was used. Spearman's correlation was used to correlate the viral load in the saliva with blood of kidney transplant recipients. Results: The mean age of the study group was 51.11±12.45 years old, and 69 participants (54.8%) were female, with a mean post-transplantation time of 4.80±6.04 months. BKPyV was quantified in several samples of saliva and blood, with medians of 1,108 cp/mL and 1,255 cp/mL, respectively. Only 16/52 (30.8%) participants presented BKPyV in blood, and 59/126 (46.8%) excreted the virus in saliva (p=0.004). BKPyV shedding was found in patients at a shorter post-transplantation period (3.86±5.25, p=0.100). A weak correlation was observed between viral quantification in saliva and blood (Spearman's correlation coefficient=0.193). Conclusion: The results of this study suggested that, although saliva excretes more BKPyV than blood, there is no reliable correlation between salivary shedding and blood viremia, showing two independent compartments of viral replication.